2006
DOI: 10.1007/s00011-006-5067-5
|View full text |Cite
|
Sign up to set email alerts
|

Taurine chloramine inhibits proliferation of rheumatoid arthritis synoviocytes by triggering a p53-dependent pathway

Abstract: We propose that Tau-Cl inhibits proliferation of RA FLS by triggering a p53-dependent cell-cycle arrest and conclude that this compound suppresses pathways in FLS that are known to contribute to the pathology of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
(80 reference statements)
0
8
1
1
Order By: Relevance
“…Kontny et al . reported that TauCl caused progressive necrosis of RA FLS at ≥500 µM [36]. However, in our previous report, TauCl toxicity seemed to vary according to the individual RA patient [16].…”
Section: Discussionmentioning
confidence: 92%
“…Kontny et al . reported that TauCl caused progressive necrosis of RA FLS at ≥500 µM [36]. However, in our previous report, TauCl toxicity seemed to vary according to the individual RA patient [16].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, in these cells TauCl down-regulates also expression of collagenases (MMP-1, MMP-13) that play a dominant destructive role in RA (Kim et al 2007, 2010a, b). Furthermore, TauCl inhibits proliferation of RA FLS and renders these cells more sensitive to death (Kontny et al 2006a, b). Thus, in vitro TauCl dampens several activities of rheumatoid FLS relevant to the contribution of these cells to local pathological processes, i.e., inflammation support, joint destruction and synovial hyperplasia.…”
Section: Taurine and Taurine Derivatives In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…It has been suggested and demonstrated for many systems that N-chloroamino acids, formed upon reaction with HOCl/OCl ( , decrease the concentration of this chlorinating agent but exert similar effects themselves. Taurine has been reported to prevent the production of nitrite and TNF-a by lung cells in the presence of myeloperoxidase-H 2 O 2 -halide system via N-chlorotaurine formation [30], but on the other hand N-chlorotaurine has also been implicated in intracellular glutathione loss [31] and apoptosis induction by triggering the p-53 dependent pathway [32]. Amine group of proteins, apart from thiols, are the major targets of HOCl/OCl ( acid attack in proteins [8].…”
Section: Discussionmentioning
confidence: 99%